If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -3 = 9x + 20 Combine like terms: -4 + -3 = -7 -7 = 9x + 20 Reorder the terms: -7 = 20 + 9x Solving -7 = 20 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -7 + -9x = 20 + 9x + -9x Combine like terms: 9x + -9x = 0 -7 + -9x = 20 + 0 -7 + -9x = 20 Add '7' to each side of the equation. -7 + 7 + -9x = 20 + 7 Combine like terms: -7 + 7 = 0 0 + -9x = 20 + 7 -9x = 20 + 7 Combine like terms: 20 + 7 = 27 -9x = 27 Divide each side by '-9'. x = -3 Simplifying x = -3
| x+64=12 | | -5x-5x= | | 15-3(x+3)=21 | | 7x+17=4x-25 | | 2n-9+3=4n+1 | | 5[1.5(x-1)-6.8]-0.31x=3.7 | | 5ln(4x)=17 | | -6b+9+2b=49 | | 4(-3+x)=6-2x | | 7a^2=32a-16 | | 5+5x-4x= | | 3h-12=33 | | 2x+11=59-8x | | 8r^2-34-9=0 | | 2a-7a=9-6a | | 4(4c-1)-4=13c+7 | | 31+5y-9=17y-14-3y | | x/13=-8 | | 8x-8=9x+8 | | -53+2i=-I+73 | | 4m+t= | | 4m+10=2m-6 | | 6-3x=14-7x | | -5(x-3)+2x=6 | | 14(2f)=7(f-2) | | 9y-(11)-(5y)=-25 | | -53-2i=-I+73 | | y/11=17 | | 6x+4=70 | | 2.4(3.1x+4.9)=75.9+0.87 | | m(m-3)=54 | | 5m-7= |